Self Assemblies of Poly(ether ether ketone) Block Copolymers for Biomedical Applications. Issue 34 (9th September 2021) - Kumar, Avneesh
Abstract: Oriented and ordered domains in an unusual engineering homopolymer known as poly ether ether ketone (PEEK) are stimulated by attaching a phosphonated ionic segment to its both ends. Such orientation of polymer chains leads to the formation of nanoparticles in solution. The ordered domains contain the stacks of rigid polymer chains that result into the crystalline regions appearing in rather unusual manner. Here, the molecular motions and reorganization are reinforced by hydrogen bonds, and not by annealing. On a silicone surface i. e. a substitute for titanium in implants, these copolymer attach via ionic groups and consequently the molecular self assemblies get disrupted. The corresponding copolymer films show submicrometer sized roughness, and hence can improve adhesion significantly. The self assemblies induced and generated simultaneously contain functional groups and can bind to a metallic surface for biomedical applications e. g. bone implants. These block copolymers as bone or dental implants can be superior to the ones based on modified PEEKs where the degree of modification can be problematic and can compromise the properties of PEEK. In addition, tri‐block copolymers described here can be better alternatives for bone implants due to their cell adhesion efficiency via ionic groups and thermal stability including reasonable biocompatibility. Abstract : Biocompatible high performance tr‐block copolymers (BCP) show morphological transformations under different environment leading to the formation of multifunctional nanoparticles and lamellar for biomedical applications e. g. bone implants.